Abnormal sonographic appearance of posterior brain at 11–14 weeks and fetal outcome. (19th May 2015) - Volpe, P.; Muto, B.; Passamonti, U.; Rembouskos, G.; De Robertis, V.; Campobasso, G.; Tempesta, A.; Volpe, G.; Fanelli, T.
Abstract Objective The aim of this retrospective study was to describe the sonographic appearance of the posterior brain anatomy in normal fetuses at 11 to 14 weeks of pregnancy and to determine the fetal outcome when one of the posterior brain anatomical space is not recognized. Methods Two groups of patients were included in the study: a control group of consecutive 311 healthy fetuses with a normal sonogram and a study group of 21 fetuses with absence of one of the three posterior brain spaces. In each fetus, images of the mid‐sagittal view of the fetal face and brain at 11 to 14 weeks of gestation were obtained. Results In all fetuses with absence of one of the three posterior brain spaces, a severe anomaly, including open spina bifida, cephalocele, Dandy–Walker complex, and chromosomal aberrations, was associated. Conclusion Our study indicates that the sonographic finding characterized by the absence of one of the three posterior brain spaces seems to facilitate not only the detection of open spina bifida, as previously reported, but also of other neural tube defects, such as cephalocele, and is an important risk factor for cystic posterior brain anomalies, and/or chromosomal abnormalities. Thus it seems a poor prognostic finding for major fetal abnormalities. © 2015 John Wiley & Sons, Ltd.